Analysis Of Heavy Metal In Refilled Drinking Water In Demak Regency Using Atomic Absorption Spectrophotometry - Yanulia Handayani; Kadar Ismah; Dwi Susiloningrum; Nova Wahyu Utami (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Drinking water is a vital necessity which must meet the health standards because it directly impacts the body's biological functions. Increasing groundwater pollution has prompted people, especially in rural areas, to turn to refilled drinking water as a practical and economical option. However, the quality of refilled drinking water remains a concern, particularly regarding the potential for heavy metals such as Pb, Fe, Cd, and Cr, which are harmful to health. This study aimed to determine the levels of those heavy metals in refilled drinking water in Demak and analyze the effects of ozone, ultraviolet, and reverse osmosis disinfection methods on metal content. This study used a quantitative descriptive approach which used nine samples from drinking water refill station in Demak with three samples for each disinfection method. Metal content was analyzed by using Atomic Absorption Spectrophotometry (AAS), while pH and organoleptic tests were used to complete the water quality evaluation. All samples had Pb, Cd, and Cr levels below the thresholds stipulated in Regulation of the Minister of Health No. 492/2010 and SNI 3553:2015. However, Fe levels in several samples exceeded the standards (0.1 mg/L according to SNI and 0.3 mg/L according to the Minister of Health Regulation), with the highest value was 0.31 mg/L. Six samples had a pH below 6.5, indicating acidic properties that could potentially accelerate corrosion and release heavy metals. Most refilled drinking water in Demak met quality standards, but required special attention to Fe and pH levels approaching or exceeding the thresholds. Keywords: Refilled drinking water, heavy metals, disinfection method, AAS